Dimensions of the Myers-Briggs Type Indicator (MBTI) and the customers’ purchase Intention - Maryam khalili yadegari; Mohammad Mahmoudi Maymand; Hamidreza Vazirzanjani (تحقیقات بازار یابی نوین, 2013)
Identifying consumers’ motivation would affect target market choice. While motivation enforces and directs consumer behavior, consumer personality also forms his choice behavior regarding his goal achievement. Mayers-Brigges Type Indicator (MBTI), according to Jung theory and psychological conflicts, indicates 16 personality types. In this research, we review how different personality types influence the individuals’ attitude toward VAIO brand image, VAIO laptop knowledge/ involvement, and purchase intention. Also, we find out whether there is any relationship among these variables. Sample of 465 laptop buyers in Tehran markets has been investigated. Buyers’ personality types and their attitude toward variables have been examined by MBTI and 7-point Likert researcher made questionnaires, respectively. The data has been analyzed by SPSS16 software. Research findings indicate that there is a relationship between individuals’ personality type and visual construct of brand image variable (laptop design). Personality types do not indicate significant differences between consumer attitude and product involvement/ knowledge and its purchase intention. Moreover, consumers’ attitude toward brand image, product knowledge/ involvement affects laptop purchase intention. Also, VAIO laptop involvement has significant effect on VAIO brand image.